A COMPARATIVE ANALYSIS OF ETIQUETTE LEXEMES IN ENGLISH AND UZBEK LANGUAGES: A LINGUISTIC PERSPECTIVE (TAMADDUN NURI JURNALI, 2024)
This scientific article presents a comparative linguistic analysis of etiquette lexemes in the English and Uzbek languages. Etiquette, as a fundamental aspect of social interaction is reflected in the lexical choices and linguistic features of these two languages. The study aims to explore the cultural and social implications of polite behavior encoded in language, shedding light on the similarities and differences in etiquette lexemes between English and Uzbek.